Identification of novel TDRD7 isoforms - Skorokhod, O.M.; Gudkova, D.O.; Filonenko, V.V. (Вiopolymers and Cell, 2011)
Aim. The aim of our study was to investigate the tudor domain-containing protein 7 (TDRD7 ) subcellular localization, which could be linked to diverse functions of this protein within the cell. Methods. In this study we employed cell imaging technique for detecting TDRD7 subcellular localization, Western blot analysis of HEK293 cell fractions with anti-TDRD7 monoclonal antibodies and bioinformatical search of possible TDRD7 isoforms in Uniprot, Ensemble, UCSC databases. Results. We have observed specific TDRD7-containing structures in cytoplasm as well as in the nucleus in HEK293 cells. The Western blot analysis of subcellular fractions (cytoplasm, mitochondria, nucleus) allowed us to detect three lower immunoreactive bands, with the aproximate molecular weight of 130, 110 and 60 kDa (we termed them as TDRD7b, TDRD7g and TDRD7d) and specific subcellular localization. The bioinformatical analysis of TDRD7 primary structure allowed us to determine two alternative transcripts from TDRD7 gene coding for proteins with calculated molecular weight of 130 and 60 kDa. Conclusion. The presented data demonstrate the existence at protein level of potential TDRD7 isoforms: TDRD7b, TDRD7g and TDRD7d. The expression profile of these splice variants and their role in cells remains to be elucidated. Keywords: TDRD7, S6 kinase, isoform, piRNAs, translation.